Patient preference study for different characteristics of systemic psoriasis treatments (Protimisis). Issue 3 (6th February 2018) - Rigopoulos, D.; Ioannides, D.; Chaidemenos, G.; Kallidis, P.; Voultsidou, A.; Matekovits, A.; Soura, E.
Abstract: "The Protimisis" study was a multicenter, cross‐sectional study investigating the relative importance and economic value that patients assign to different characteristics of systemic psoriasis treatments. Treatment preferences were investigated with the DCE methodology and patients had to decide over the most important aspects of different psoriasis treatments. A questionnaire regarding demographic data/medical history and the DLQI and EQ‐5D‐3L questionnaires were also completed. A total of 310 patients were included. Out of those, 37.4% reported using oral medications for psoriasis as their most recent treatment, while the remaining patients reported treatment with injections once per week (14.8%), injections twice per week (7.4%), injections once every three months (29.4%) and intravenous injections every two months (8.4%) as their most recent treatment. Mean DLQI score was 6.6 (SD 6.5), and in the EQ‐5D‐3L index, 71.0% of patients reported having problems with anxiety or depression. DCE analysis showed a clear preference for treatments with longer dosing intervals, rapid onset of action, lasting clinical response, low risk of SAEs and lower cost. The risk of SAEs was the most important treatment characteristic (54% of patients). Older patients showed less concern for safety matters than younger patients. The highest willingness‐to‐pay was recorded for treatments with longer dosing intervals and for safer treatment options.